Optimization of distribution lines based on "Farm-link-supermarket" - Yan Feng Li (2018)
"Farm-link-supermarket" (FLS), that is "peasant households + specialized farmers cooperatives + supermarkets", is a modern distribution model which facilitates the flow of fresh and live agricultural products from farm to supermarket, with the lowest price and the best quality. The implementation of this creative model requires the support of modern logistics, which includes the integration of cash flow, logistics and information flow, the proper arrangement of transportation, warehousing, distribution and etc, as well as the implementation of supplying and logistics agreement among farmers, suppliers in all levels, and supermarkets. Based on the analysis of FLS mode, this paper applies Sierpinski curve algorithm to optimize the TSP problem. The purposes of it are to reduce circulation cost, and improve the efficiency of distribution and service level.